A new species of Uroxys Westwood, 1842 (Coleoptera: Scarabaeidae: Scarabaeinae) from central Brazil, and taxonomical remarks on Uroxys epipleuralis (Boucomont, 1928) - Nazaré-Silva, Everton E.; Moura, Ana B.g.; Silva, Fernando A.b. (Zootaxa, 2023)
Uroxys punctatus, new species, is described from central Brazil based on taxonomic characters in the cephalic and pronotal punctations and in the male genitalia. A comparative diagnosis with U. epipleuralis (Boucomont, 1928), a morphologically similar species, is provided. A lectotype is designated for U. epipleuralis from a series of four syntypes. Uroxys thoracalis Balthasar, 1940 is newly established as a junior subjective synonym of U. epipleuralis, whereas the previously proposed synonymy between the latter and U. dureti Martínez, 1947 is confirmed. Both nomenclatural acts are based on the study of the respective type specimens. A detailed literature review, illustrations of diagnostic characters, and distributional data for each species are provided.